Review of Bennet Zon. 2007. Representing Non-Western Music in Nineteenth-Century Britain. Rochester, NY: University of Rochester Press - Revuluri, Sindhumathi (Current Musicology, 2009)
Bennet Zon’s Representing Non-Western Music in Nineteenth-Century Britain surveys British Primary sources from the “long” nineteenth century that describe, theorize, and react to various types of music from around the world. Zon shows how discourse around non-Western music in this time and place was shaped by and indebted to the broad intellectual trends in anthropology and psychology, as well as musicology and travel literature. Zon states that this study is mean to rectify the lacuna around how composers or the general populace may have perceived non-Western musics, not simply the way they were imagined in classical compositions. A parallel aim of this study appears explicitly in the epilogue, and deals with establishing a history of British ethnomusicology and redeeming previously overlooked innovators as particular agents in that history.